A New Window of Opportunity for Siberian Farmers. Issue 4 (3rd April 2018) - Ovsepyan, Karen; Veselova, E.Sh.
Abstract : In August 2016, the construction of a railway terminal for the export of Russian grain to China began in Zabaikalsk. The project is operated by ООО Siberian Grain Terminal. The company's CEO, Karen Ovsepyan, spoke with EKO about the project during the Twelfth Grain Roundtable in Novosibirsk.